2017
DOI: 10.4102/ac.v17i1.366
|View full text |Cite
|
Sign up to set email alerts
|

The familiar versus the unfamiliar: Familiarity bias amongst individual investors

Abstract: Purpose: The purpose of this study was to investigate the existence of familiarity bias amongst individual investors in the South African stock market. Problem investigated: According to Warren Buffet, one needs to maintain emotional detachment if one wants to be a successful investor. However, recent research indicates that the perceptions of companies’ products and brands may influence individuals’ investment decisions in the stock market. This phenomenon implies that the investment decisions of individual i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 34 publications
0
24
1
1
Order By: Relevance
“…Despite the growing body of research on online trading platforms, there is still lack of understanding about the impact of perceived security risk, perceived privacy risk, perceived financial risk and perceived fraud risk on investor trust as well as the intention to invest in online trading platforms in Africa. Precisely, within the South African context previous studies have conducted their studies in various contexts by focusing on the relationship between foreign direct investment and economic growth in South Africa (Masipa 2018); a few South African cents' worth on Bitcoin (Nieman 2015); the relationship between the exchange rate and the trade balance in South Africa (Chiloane, Pretorius & Botha 2014); responsible investing in South Africa (Viviers & Els 2017); familiarity bias among individual investors (De Vries, Erasmus & Gerber 2017) and a South African perspective on the investment performance of ethical funds compared to conventional funds and investor behaviour as regards ethical funds (Patel 2016). This shows that there is scant evidence of studies focusing on how perceived security risk, perceived privacy risk, perceived financial risk and perceived fraud risk impact investor trust and the intention to invest in online trading platforms in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing body of research on online trading platforms, there is still lack of understanding about the impact of perceived security risk, perceived privacy risk, perceived financial risk and perceived fraud risk on investor trust as well as the intention to invest in online trading platforms in Africa. Precisely, within the South African context previous studies have conducted their studies in various contexts by focusing on the relationship between foreign direct investment and economic growth in South Africa (Masipa 2018); a few South African cents' worth on Bitcoin (Nieman 2015); the relationship between the exchange rate and the trade balance in South Africa (Chiloane, Pretorius & Botha 2014); responsible investing in South Africa (Viviers & Els 2017); familiarity bias among individual investors (De Vries, Erasmus & Gerber 2017) and a South African perspective on the investment performance of ethical funds compared to conventional funds and investor behaviour as regards ethical funds (Patel 2016). This shows that there is scant evidence of studies focusing on how perceived security risk, perceived privacy risk, perceived financial risk and perceived fraud risk impact investor trust and the intention to invest in online trading platforms in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis showed that the hypothesis H3 brand familiarity platform supported mutual funds affect the interests investasiDalam financial behavior theory (Behavioral Finance Theory) states that the investment decision of a person can be influenced by a person's emotional and cognitive factors. The sense of familiar and unfamiliar to a brand it will display the confidence and desire to continue to use or even pulled sacrifice of investing money for the companies that are considered familiar.Brand familiaritymay be one reason to invest because of humans is a subject that has emotions can be influenced by the environment, eg a company or a brand of the most frequent and convenient to use [6,20]. The proximity and experience (familiarity), realistic, self-control and social interaction does not have a significant effect on the behavior of an investor to make his choice in investing [19].…”
Section: Third Hypothesis Testing Resultsmentioning
confidence: 99%
“…This study departs from the assumption that the deviation of company stock prices is caused by investors who act irrationally (Barberis & Thaler, 2002). This implies that an investor's investment decision is not based on a company's fundamental analysis but is based on investors' perceptions of a company or brand (De Vries, Erasmus, & Gerber, 2017).…”
Section: Literature Review Behavioral Financementioning
confidence: 91%
“…When doing investment activities, an investor not only judges based on the fundamental analysis of a company but also sees based on the perceptions they build on a company or brand. (De Vries, Erasmus, & Gerber, 2017). This statement is contrary to traditional financial theory which assumes that human behavior when making decisions is rational and financial market conditions are described as efficient markets (Yalcin, Tatoglu, & Zaim, 2016).…”
Section: Introductionmentioning
confidence: 90%